Exogenous Melatonin Mitigates Photoinhibition by Accelerating Non-photochemical Quenching in Tomato Seedlings Exposed to Moderate Light during Chilling - Ding, Fei; Wang, Meiling; Liu, Bin; Zhang, Shuoxin (Frontiers in Plant Science, 2017)
Melatonin plays an important role in tolerance to multiple stresses in plants. Recent studies have shown that melatonin relieves photoinhibition in plants under cold stress; however, the mechanisms are not fully understood. Non-photochemical quenching (NPQ) is a key process thermally dissipating excess light energy that plants employ as a protective mechanism to prevent the over reduction of photosystem II. Here, we report the effects of exogenous melatonin on non-photochemical quenching and mitigation of photoinhibition in tomato seedlings exposed to moderate light during chilling. In response to moderate light during chilling, the maximum quantum yield (Fv/Fm) and the effective photochemical efficiency (F′v/F′m) of PSII were both substantially reduced, showing severe photoinhibition in tomato seedlings, whereas exogenous application of melatonin effectively alleviated the photoinhibition. Further experiment showed that melatonin accelerated the induction of NPQ in response to moderate light and maintained higher level of NPQ upon longer exposure to light during chilling. Consistent with the increased NPQ was the elevated de-epoxidation state of xanthophyll pigments in melatonin-pretreated seedlings exposed to light during chilling. Enzyme activity assay showed that violaxanthin de-epoxidase (VDE), which catalyzes the de-epoxidation reaction in the xanthophyll cycle, was activated by light and the activity was further enhanced by application of melatonin. Further analysis revealed that melatonin induced the expression of VDE gene in tomato seedlings under moderate light and chilling conditions. Ascorbic acid is an essential cofactor of VDE and the level of it was found to be increased in melatonin-pretreated seedlings. Feeding tomato seedlings with dithiothreitol (DTT), an inhibitor of VDE, blocked the effects of melatonin on the de-epoxidation state of xanthophyll pigments and the induction of NPQ. Collectively, these results suggest that exogenous melatonin mitigates photoinhibition by accelerating NPQ through the stimulation of VDE activity and the enhancement of de-epoxidation state of xanthophyll pigments.